Reliability of shear-wave elastography (SWE) for investigating cervix elastic properties in normal and benign pathological situations - Laura Castro; Jose Antonio García-Mejido; Ainhoa Holgado; Rocio García; Ana Fernández-Palacín; Jose Antonio Sainz (IMR Press, 2021)
Background: Our aim in this study is to evaluate the inter- and intraobserver correlation of the different shear-wave elastography (SWE) parameters (stiffness) in both control and pathological groups. Methods: Evaluations of cervical stiffness measurements were performed in 39 non-pregnant patients (21 cases without gynecological pathology and other 18 cases with cervical preinvasive cervical lesion susceptible to conization) aged between 18-65 years old, without vaginal infection other than HPV and without another gynecological pathology. We used SWE (shear modulus) endovaginal ultrasound. We performed the evaluation in the midsagittal plane of the uterine cervix with measurements at 0.5, 1 and 1.5 cm from external cervical OS, in both anterior and posterior cervical lips as well as the cervical canal. Sonoelastography was performed by two examiners, each one making two separate assessments of uterine cervical stiffness using SWE, in one single visit. Interclass correlation coefficients (ICC) with 95% CIs were used to assess intra and interobserver measurements repeatability. Results: We obtained an adequate intra and interobserver correlation (ICC 0.996-0.999) of stiffness in all anatomical sites both in normal and pathologic cervix (p < 0.005). The stiffness in normal cervix is from 38.28 ± 19.76 kPa vs to 61.58 ± 27.54 kPa in the pathological cervix. Conclusion: The SWE has an adequate intra and interobserver correlation for its use in evaluating both normal and pathological cervix.